PENGARUH DAYA SAING DAN AKSES PEMASARAN TERHADAP KINERJA PEMASARAN - Hendriyanto, Asepta (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2017)
This study is to determine what factors affect the performance of SMEs. The population in this study are all the owner of SMEs in the Central Java. Sampling was conducted with a purposive sampling criteria were used in the consideration that SMEs are already running at least five years. The sample in this study is intended as representative of the population to be studied, totaling 67 (sixty seven). The data were then processed andanalyzed by using the computer program of SPSS 20 for Windows. Based on the results of testing the partial regression analysis can be concluded: The competitiveness and marketing access is partially affect performance significantly and positively. This means that the higher competitiveness and marketing access the higher performance. Meanwhile, competitiveness and marketing access have influence on SME’s performance through network capabilities.